West African agriculture and climate change: A comprehensive analysis - Sierra Leone - Johnson, Raymond G.; Kandeh, Mohamed; Jalloh, Abdulai; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
Agriculture is the largest sector in the Sierra Leone economy, employing more than 75 percent of labor force and contributing be-tween 35 and 47 percent of GDP. Rice, the staple food crop, is grown mainly by small-scale farmers under rainfed conditions. Transporting produce remains a challenge, as most of the roads in remote areas are impassable during the rainy season.